A Randomized, Placebo‐Controlled, Double‐Blind Phase III Trial Investigating the Efficacy and Safety of IncobotulinumtoxinA in the Treatment of Glabellar Frown Lines Using a Stringent Composite Endpoint. Issue 6 (18th March 2013) - William Hanke, C.; Narins, Rhoda S.; Brandt, Fredric; Cohen, Joel L.; Donofrio, Lisa M.; Downie, Jeanine; Heinz, Moritz; Harrington, Laura; McDaniel, David H.; Nestor, Mark; Schlessinger, Joel; Schlöbe, Andrea; et al.
Abstract : Background: A prospective, randomized, double‐blind, multicenter, Phase III trial of incobotulinumtoxinA using new Food and Drug Administration endpoints. Objective: To investigate the efficacy and safety of a single dose of incobotulinumtoxinA for the treatment of glabellar frown lines. Materials and Methods: Two hundred seventy‐one subjects with moderate to severe glabellar frown lines at maximum frown—as assessed by an investigator according to the facial wrinkle scale (FWS)—were randomized 2:1 to receive one treatment of 20 U of incobotulinumtoxinA or placebo, respectively, and assessed over 120 days. The primary efficacy variable was a composite endpoint consisting of patients who were 2‐point or more responders at maximum frown on Day 30 according to the investigator's rating on the FWS, and 2‐point or more responders at maximum frown on Day 30 according to the patient's assessment on a 4‐point scale. Safety analyses were performed throughout the study. Results: IncobotulinumtoxinA was statistically significantly more efficacious than placebo using a new rigorous composite endpoint ( p  < .0001). Conclusion: A single dose of 20 U of incobotulinumtoxinA is superior to placebo in the treatment of glabellar frown lines at Day 30 and is well‐tolerated.